Human protectin (CD59), an 18,000-20,000 MW complement lysis restricting factor, inhibits C5b-8 catalysed insertion of C9 into lipid bilayers. - Meri, S; Morgan, B; Davies, A; Daniels, R; Olavesen, MG; Waldmann, H; Lachmann, P (1990)
Human cells are relatively resistant to lysis by the homologous complement system. Here we describe the mechanism of action of a recently discovered and widely distributed 18,000-20,000 molecular weight (MW) membrane glycoprotein (CD59), which appears to act as a major protective element against complement-mediated lysis (hence called protectin). When incorporated into heterologous erythrocyte membranes, protectin efficiently prevented cell lysis by human serum. Neutralization with antibody of the naturally occurring protectin on human erythrocytes or on nucleated K562 cells increased their susceptibility to lysis by homologous complement. During complement activation, protectin became incorporated into the membrane attack complex (MAC). By interacting with newly exposed regions in the C5b-8 complex and in aggregating C9 it limited the number of C9 molecules associating with the C5b-8 complex to a C8:C9 ratio of 1:1.5 instead of a normal average of 1:3.5. The results demonstrate directly that protectin is a powerful inhibitor of complement cytolysis and acts by inhibiting the C5b-8 catalysed insertion of C9 into the lipid bilayer.